2020
DOI: 10.48550/arxiv.2006.16227
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Local Singularity Analysis for the Ricci Flow and its Applications to Ricci Flows with Bounded Scalar Curvature

Abstract: We prove that Ricci flows with bounded scalar curvature cannot develop finite time singularities in dimensions less than eight. In order to study such flows in higher dimensions, we then develop a refined singularity analysis for the Ricci flow by investigating curvature blow-up rates locally. We first introduce general definitions of Type I and Type II singular points and show that these are indeed the only possible types of singular points. In particular, near any singular point the Riemannian curvature tens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…In dimension three, this is a consequence of the Hamilton-Ivey pinching estimate(see [25]) while in higher dimensions it is known to be true for (globally) Type I Ricci flows by Ender, Müller and Topping [12] as well as in the Kähler case by Zhang [28]. In recent years, this conjecture has been the focus of many many interesting new developments, see for example [2], [5], [6], [7], [8], [9], [10], [12], [22], [23], [27], [28].…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…In dimension three, this is a consequence of the Hamilton-Ivey pinching estimate(see [25]) while in higher dimensions it is known to be true for (globally) Type I Ricci flows by Ender, Müller and Topping [12] as well as in the Kähler case by Zhang [28]. In recent years, this conjecture has been the focus of many many interesting new developments, see for example [2], [5], [6], [7], [8], [9], [10], [12], [22], [23], [27], [28].…”
Section: Introductionmentioning
confidence: 93%
“…From the perspective of globally Type I or Type II, we can only analyze singularities of such Types. To analyze pointwisely singularities of Ricci flows, Buzano and Di-Matteo [7] introduced general definitions of locally Type I and locally Type II singular points (see Definition 3.1 below). Our main result in this paper is implicitly directed towards proving the same assertion in ( * ) in the local sense in dimension < 8 (exact claim is Main Theorem mentioned above).…”
Section: Backgroundsmentioning
confidence: 99%
See 2 more Smart Citations
“…scalar curvature [BZ17]. Even more recently however, it has been shown that Ricci flows on a closed Riemannian manifold of dimension less than 8 with bounded scalar curvature exist for all time: [BD20]. Finally, ALE Ricci flat metrics actually appear as finite-time blow-up limits of some Ricci flows [App19].…”
Section: Introductionmentioning
confidence: 99%